Defining the Boundaries of KPK Authority Through Integrating the KPK and Anti-Corruption Laws - NI MADE ANGGITA SASTY YUDIADEWI; I Gusti Bagus Suryawan; Kade Richa Mulyawati (Veteran Law Review, 2026)
The eradication of corruption in Indonesia still faces significant legal challenges, particularly regarding the boundaries of authority between law enforcement institutions. The Corruption Eradication Commission (KPK) often encounters overlapping jurisdictions with the National Police and the Attorney General's Office, which leads to legal uncertainty and institutional friction. This study aims to analyze the specific boundaries of the KPK's authority in the investigation and prosecution of corruption cases through the strategic integration of the KPK Law and the Anti-Corruption Law (UU Tipikor). The research method employed is normative legal research, utilizing a statutory approach and a conceptual approach to examine existing regulations. The results of this study indicate that the current lack of synchronization between these two primary laws creates a gray area in law enforcement operations. Therefore, a comprehensive integration between the KPK Law and the Anti-Corruption Law is urgently needed to clarify the limits of authority and strengthen the institutional coordination function. This integration is expected to optimize the synergy of law enforcement in Indonesia, creating an effective, efficient, and integrated corruption eradication system that upholds the principles of legal certainty and justice for the public.